Emergence of plasmid-mediated colistin resistance (MCR-1) among Escherichia coli isolated from South African patients - Coetzee, Jennifer; Corcoran, Craig; Prentice, Elizabeth; Moodley, Mischka; Mendelson, Marc; Poirel, Laurent; Nordmann, Patrice; Brink, Adrian John (South African medical journal, 2016)
The polymyxin antibiotic colistin is an antibiotic of last resort for the treatment of extensively drug-resistant Gram-negative bacteria, including carbapenemase-producing Enterobacteriaceae. The State of the World's Antibiotics report in 2015 highlighted South Africa (SA)'s increasing incidence of these 'superbugs' (3.2% of Klebsiella pneumoniae reported from SA were carbapenemase producers), and in doing so, underscored SA's increasing reliance on colistin as a last line of defence. Colistin resistance effectively renders such increasingly common infections untreatable.